Porównanie metod estymacji parametrów i wyboru modeli stóp procentowych - Mruklik, Agnieszka (Comparison of Estimation Methods of Parameters and Choice Manners of Interest Rates Models, 2006)
In the paper, we consider the problem of comparison between statistical estimation and calibration for Ornstein-Uhlenbeckean model of instantaneous interest rate r(t). Furthermore, we describe different approximation methods of realizations of process r(t). We study the influence of these approximations on estimators. Moreover, some methods of computer simulations have been also described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 369-380